CLASSROOM TO VIRTUAL WORLD: APPLYING THE METAVERSE IN RESEARCH TO IMPROVE THE QUALITY OF TEACHING AND LEARNING - Pastraporn Thipayasothorn (Journal of Industrial Education, 2025)
Classroom to the Virtual World: Applying Virtual Universes to Research to Enhance Teaching Quality article describes approaches to integrating virtual world technology with classroom research processes to enhance the quality of learning in the 21st century. Technological transitions, particularly virtual reality (VR), augmented reality (AR), and Web 3.0, have opened the door for Thai education to enter the "virtual classroom." Connecting learners with real-world experiences through digital environments, virtual worlds enable teachers to design highly interactive learning practices, simulate real situations, and record learning behavioral data for in-depth analysis. Classroom research can thus apply data from virtual worlds to systematically reflect teaching outcomes. It also promotes "co-creational learning" and learners' intrinsic motivation. Developments across the dimensions of learners, teachers, and learning systems result in "virtual learning communities" that connect learners from diverse backgrounds. This article proposes that integrating virtual worlds with classroom research involves not just a change in media formats but also a shift in educational paradigms toward experiential learning and collaborative knowledge creation. This is to propel the quality of Thai teaching and learning to keep pace with the changes in the digital age.
Keywords: Virtual Reality Applications and Impacts; Visual and Cognitive Learning Processes; Online and Blended Learning